2015
DOI: 10.1093/rheumatology/kev313
|View full text |Cite
|
Sign up to set email alerts
|

A high body mass index is associated with reduced risk of rheumatoid arthritis in men, but not in women

Abstract: A high BMI was associated with a reduced risk of future RA in men, but not in women. Factors related to adipose tissue may contribute to mechanisms that are protective from RA in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 32 publications
3
38
2
Order By: Relevance
“…In the present study we could not find support for a differentiated role for obesity according to the serologic status of RA, as some previous studies have indicated [7, 8, 15]. From this perspective we suggest that obesity, abdominal obesity and/or factors related to these, act as a trigger or drive on the inflammatory system(s), rather than exert a specific immunologic effect.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study we could not find support for a differentiated role for obesity according to the serologic status of RA, as some previous studies have indicated [7, 8, 15]. From this perspective we suggest that obesity, abdominal obesity and/or factors related to these, act as a trigger or drive on the inflammatory system(s), rather than exert a specific immunologic effect.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study the association between obesity and RA was seen mainly for early disease onset among men, and the Nurses’ Health Study included women exclusively, which makes the results difficult to compare [6]. Interestingly, our results contradict the results from a Swedish study in which high BMI in some regression models were associated with a reduced risk of RA in men, who compared with our study, were examined at a higher age [7]. If obesity acts as a strong trigger for disease onset at an early age in predisposed men, the selection of older age at examination could theoretically have contributed to an apparent protective effect.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Again, these results vary in recent studies. While some studies have shown similar results in men and women [12•, 22•], others have suggested that obesity may be associated with a decreased risk of RA among men [19••, 24]. Some studies have also shown an association between obesity and RA only in younger subgroups [12•, 20••], and it has been proposed that an effect specific to younger individuals might explain why no association between obesity and RA has been identified in some older cohorts [22•].…”
Section: Obesity and The Risk Of Developing Ramentioning
confidence: 96%
“…In addition, the relationship between obesity and RA risk is conflicting. One study has shown that an increasing body mass index (BMI) was protective against RA development in men, although there was no significant relationship with RA risk in women (94). Another study showed that an increasing BMI was a risk factor for RA in both men and women, but less so in women (95).…”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%